TAKAYASU'S ARTERITIS FOLLOWING HIDRADENITE SUPURATIVA IN A YOUNG WOMAN: A CASE REPORT OF A RARE ASSOCIATION - Saldanha, Ana Beatriz Lacerda Costa; Souza, Ana Beatriz Lopes; Cavalcante, André Sobreira; Matias, Bruna Pessoa; Portugal, Chiara Gübel; Fernandes, João Victor Viana; Freitas, Lara Maria de Oliveira Paiva; Bastos, Lêda Maria Veloso; de Oliveira, Luciana Maria Pereira (ARACÊ, 2025)
Hidradenitis suppurativa, Takayasu's arteritis, and ankylosing spondylitis are chronic inflammatory diseases with distinct pathophysiologies that rarely coexist. We report the case of a 25-year-old female patient diagnosed with all three conditions. Initially presenting with recurrent erythematous lesions and abscesses in childhood, she was diagnosed with hidradenitis suppurativa at age 16 and treated with adalimumab. At 22, she developed inflammatory back pain, leading to a diagnosis of ankylosing spondylitis and subsequent treatment with infliximab. Later, symptoms of systemic vasculitis emerged, and imaging confirmed Takayasu's arteritis. This case highlights a rare association between these diseases, emphasizing shared immune mechanisms and the need for multidisciplinary care.